A drip-crosslinked tough hydrogel. (17th January 2018) - Zhang, Yu; Yong, You; An, Duo; Song, Wei; Liu, Qingsheng; Wang, Longhai; Pardo, Yehudah; Kern, Vanessa R.; Steen, Paul H.; Hong, Wei; Liu, Zheng; Ma, Minglin
Abstract: Hydrogels with good mechanical properties have received intense interests recently. Simplifying the method to prepare tough hydrogels and meantime incorporating additional properties such as anti-swelling, self-recovery, healing ability, facile processability, and recyclability will likely expand their applications significantly. Here we report a simple method to prepare tough hydrogels: dripping a carboxylated polyvinyl alcohol solution into an Al 3+ crosslinking medium. The hydrogels became even tougher after equilibrium in DI water. These drip-crosslinked tough hydrogels exhibited anti-swelling, self-recovery, acid assisted healing and great processability, and could be recycled. Interestingly, by tuning the kinetics of dripping and crosslinking, we could make tough hydrogel particles with both conventional spherical shape and various other controllable, unusual shapes such as half-sphere, tear-drop, mushroom-like and rings. We also demonstrated the possibility of using electrospraying to mass-produce uniform, micron-sized tough hydrogels. Graphical abstract: Highlights: A versatile tough hydrogel is prepared through a simple dripping process. The hydrogel possesses robust mechanical property, great self-recoverability, processability, and recyclability. By tuning the crosslinking kinetics, tough hydrogel particles with various controllable and unusual shapes are obtained. Using electrospraying technique, uniform micro-sized tough hydrogels are produced at a mass production rate.